The influence of coordination and organizational culture on the effectiveness of the management of Regional Original Income in the Regional Revenue Management Agency in Sumedang Regency, West Java Province - Ryan Bramiyanto Praja (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
This study aims to analyze the problem: How big is the influence of coordination andorganizational culture on the effectiveness of the management of Regional Original Income inthe Regional Revenue Management Agency in Sumedang Regency, West Java Province. Theresearch method uses quantitative methods, with the first independent variables Coordination,the second independent variable Organizational Culture and the dependent variableEffectiveness. The study population was all employees of the Sumedang Regency RegionalRevenue Management Agency totaling 137 people. The sampling technique uses saturatedsamples which means that all populations are made as research respondents. Data collectiontechniques are carried out with documentation studies and field studies through observation,interviews and questionnaire distribution. Data analysis techniques using statistical analysiswith path analysis models. Based on the fact, it is advisable to restructure the organizationalwork system through a Regional Head (Bupati) policy, complete the need for work facilities tostreamline the implementation of work duties, conduct employee coaching to improve employeework discipline, and conduct guidance, direction and assistance on the execution of employeeduties. so that employees can carry out their work independently. With these steps, it is expectedthat the effectiveness of the implementation of tasks can be realized optimally.